Effects of biomass, COD and bicarbonate concentrations on fermentative hydrogen production from POME by granulated sludge in a batch culture - Mohammadi, P.; Ibrahim, S.; Mohamad Annuar, M.S. (2012)
Effects of three selected variables viz. biomass concentration, initial chemical oxygen demand (COD) concentration and initial bicarbonate alkalinity (BA) on biological hydrogen production from palm oil mill effluent (POME) using the granulated sludge in batch culture were investigated. The experimental results were analyzed and modeled using a central composite design (CCD) of response surface methodology (RSM). In order to carry out a comprehensive analysis of the biohydrogen production process, indicative parameters namely hydrogen yield (Y H), specific hydrogen production rate (SHPR), and COD removal efficiency were studied as the process responses. Maximum hydrogen yield (124.5 mmol H 2/g COD removed) and specific hydrogen production rate (55.42 mmol H 2/g VSS.d) were achieved at COD in 3000 and 6500 mg/l, MLVSS 4000 and 2000 mg/l, and initial BA 1100 mg CaCO 3/l, respectively. Copyright Â© 2012, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.